Giving visibility to the invisible - Embedding gendered patterns of work intensity in agriculture-nutrition research - Zanello, Giacomo (University of Reading, 2019)
Presented by Giacomo Zanello (University of Reading), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.